Advertisement for Hercules Thanite - Hercules Incorporated (1943 Hercules Advertisements, 1943)
Advertisement for Thanite, a toxicant manufactured and sold by the Hercules Powder Company for use in pesticides and insecticides. This advertisement appeared in the June 1943 issue of Soap. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Chemical industry; Hercules Incorporated; Insect pests--Control; Corporations; Naval stores; Thanite; Insecticides; Advertising, Industrial; Insect pests